PENGUKURAN STATUS GIZI SECARA ANTROPOMETRI DI TK TAMAN INDAH PEMATANGSIANTAR - Dian Permata Nasution; Marolop Parlindungan Napitu; Yeni Trisna Purba; Isa Harpika Br. Ginting; Yosni Handayani Gea (Nusantara Hasana Journal, 2023)
This study assesses the nutritional status of children at Taman Indah Kindergarten, Pematangsiantar, using anthropometric methods to enhance human resource quality from early ages. The approach included measurements of weight, height, and mid-upper arm circumference, along with educational sessions for teachers and parents on the importance of a balanced diet for child development. Findings reveal notable gaps: a lack of routine nutrition monitoring, limited nutrition literacy among educators and parents, and insufficient collaboration with health agencies. The descriptive observational design included all enrolled students, aiming to raise awareness of nutritional issues and promote proactive, findings-based interventions for child nutrition improvement. The results underscore the need for improved nutrition monitoring programs, enhanced nutrition literacy among school facilitators, and stronger collaboration with local health authorities to prevent stunting, given a regional stunting prevalence of 14.3%.